Keterlibatan Orang Tua dalam Kegiatan Bermain Anak Usia Dini di Rumah - Yusuf Maronta; Aisyah Durrotun Nafisah (Journal Ashil: Jurnal Pendidikan Anak Usia Dini, 2024)
Many parents work outside the home fora long duration of time, making parents less involved in childcare, especially in their play activities. The purpose of this study is to describe and analyze parents' participation in children's play activities at home. The targets of this study were five households with children (5-6 years old). In Kalongan village, East Ungaran, there are working and unemployed parents. This research was designed using a descriptive qualitative method. Interview, observation, office research, documentary research and triangulation were used as data collection techniques. The results showed that parents who participated in play activities at home during childhood were mostly the same, i.e. working and unemployed parents with advanced education and moderate economic status. Then the type of parents with a weak economic background is also decreasing. On the other hand, the participation of other people in children's activities depends on the size of the family.